Collaboration between architects and planners in an urban design studio: potential for interdisciplinary learning. (28th January 2008) - Hirt, Sonia; Luescher, Andreas
Design professionals need to acquire competencies in interdisciplinary, collaborative design practice. Proceeding from this assumption, this paper analyses a case study of a joint project between an architecture studio at Bowling Green State University and a planning seminar at the University of Toledo. Students working in extramural teams developed proposals for the revitalisation of a plaza in Toledo, a historic city in Ohio. The plaza, which in architectural terms represents a blend of Gilded-Age finery, high-order contemporary work and stretches of decay, is in the process of slow regeneration. The main goals were: 1) pedagogical ? to enhance the students' learning experiences by providing them with the opportunity to work in interdisciplinary teams; and 2) research-orientated ? to examine the differences, if any, in design approaches between the architectural and the planning students. Summary outcomes include an enhanced understanding of the architectural-planning differences and a greater appreciation of the potential for mutual learning.